Public Expenditure and Financial Accountability Assessment : Nepal PFM Performance Assessment II - Government of Nepal Ministry of Finance (World Bank, Kathmandu, 2015)
The objective of this assessment is to update the public expenditure and financial accountability (PEFA) assessment published in early 2008. The assessment is expected to assist the Government of Nepal to: (a) establish indicator led assessment of the country’s public financial management (PFM) system, (b) update the fiduciary environment of the PFM systems and processes of the country, and (c) assist in identifying those parts of the PFM system that may need further reform and development. The institutional and organizational approach taken by the Government of Nepal ensured coordination among various government institutions. The assessment included collection of additional documentation, including meeting minutes, and interviews with government counterpart teams and main stakeholders. The report was updated and refined following advice from a World Bank team. A specialist in the use of PEFA methodology assisted in the later drafts and visited Nepal in August 17-20, 2014. Meetings were held with the PEFA Secretariat at the Financial Comptroller General Office (FCGO) and with the Ministry of Finance (MoF) Budget Division. This final draft of the report addresses all the comments received up to November 31, 2014. The findings of the assessment were shared with the donors in September 2014 and their comments assisted the finalization of the draft report. The World Bank also provided continuous quality control support.